Pemanfaatan Sistem Informasi Geografis (SIG) dalam Manajemen Ladang Pertanian - Evi Nursyifa; Tarwiyati T; Aura Salsabila; Minali Fazly; Yusril Y; Novia Yunanda (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Geographic Information Systems (GIS) are technologies that play an important role in managing spatial data and supporting location-based decision-making. In the agricultural sector, GIS is utilized to improve the effectiveness and efficiency of farmland management. This article aims to examine the utilization of Geographic Information Systems (GIS) in agricultural land management through a literature study approach. The method involves collecting and analyzing various literature sources, such as scientific journals, books, and relevant articles related to the application of GIS in agriculture. The results of the review indicate that GIS can support land mapping, land suitability analysis, monitoring of soil and crop conditions, and better agricultural planning. The use of GIS enables more optimal, sustainable, and data-driven agricultural land management.